Requirements for the Development of Halal Food Quality Management System in Malaysia - Abdul Latif, Mariam (2004)
To the Muslims, food must not only be of good quality but must be truly halal, hence the study of halal food quality system was initiated. All foods are halal except those that are specifically mentioned in the Quran as haram. The increasing demand for global halal food estimated at USD 150 billion is in tandem with the increasing Muslim population of approximately 2 billion people. To tap this lucrative market, Malaysia should develop a comprehensive Halal Food System to assure the quality and authenticity of its halal food. The Halal Food System encompassing the laws, the enforcement team and the support of analytical facilities should be well coordinated to gain continuous confidence from Muslims worldwide.